2002
DOI: 10.2307/3099969
|View full text |Cite
|
Sign up to set email alerts
|

Net Primary Productivity of a CO 2 -Enriched Deciduous Forest and the Implications for Carbon Storage

Abstract: A central question concerning the response of terrestrial ecosystems to a changing atmosphere is whether increased uptake of carbon in response to increasing atmospheric carbon dioxide concentration results in greater plant biomass and carbon storage or, alternatively, faster cycling of C through the ecosystem. Net primary productivity (NPP) of a closed-canopy Liquidambar styraciflua (sweetgum) forest stand was assessed for three years in a free-air CO 2 -enrichment (FACE) experiment. NPP increased 21% in stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
144
3
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 101 publications
(156 citation statements)
references
References 20 publications
8
144
3
1
Order By: Relevance
“…Processes of down-regulation are often attributed to imbalances between source-sink relationships (Urban et al 2003). However, we did not observe differences in the accumulation of NSC on leaf/needle between CO 2 treatments ( The increase in root biomass in both species at high levels of CO 2 suggests a shift in the allocation of carbon to the root system (Norby et al 2002). This flux could be especially relevant in Norway spruce which showed a significant increase in the concentration of NSC in roots.…”
Section: Response Of Growth To Admixture and Co 2 Enrichmentcontrasting
confidence: 51%
See 1 more Smart Citation
“…Processes of down-regulation are often attributed to imbalances between source-sink relationships (Urban et al 2003). However, we did not observe differences in the accumulation of NSC on leaf/needle between CO 2 treatments ( The increase in root biomass in both species at high levels of CO 2 suggests a shift in the allocation of carbon to the root system (Norby et al 2002). This flux could be especially relevant in Norway spruce which showed a significant increase in the concentration of NSC in roots.…”
Section: Response Of Growth To Admixture and Co 2 Enrichmentcontrasting
confidence: 51%
“…Indeed, we observed a significant correlation between root biomass and NSC concentration for Norway spruce (r = 0.71, P = 0.009), whereas we did not observe this effect in European beech (r = 0.52, P = 0.175). High root NSC concentrations in trees exposed to high levels of CO 2 can be interpreted as an accumulation of substrate available to support the production of fine-roots (Norby et al 2002). However, both species increased their fine root biomass at elevated levels of CO 2 Figure 5 Leaves / needles and roots non-structural carbohydrates concentration (NSC, mg / g) mean values (± S.E) of European beech and Norway spruce per CO 2 treatments, ambient and elevated.…”
Section: Response Of Growth To Admixture and Co 2 Enrichmentmentioning
confidence: 99%
“…To date, existing experiments have demonstrated that rising atmospheric [CO 2 ] results in increases in net primary production (NPP) and C storage in forest vegetation, e.g. (Calfapietra et al, 2003;DeLucia et al, 1999;Gielen et al, 2005;Hamilton et al, 2002;Handa et al, 2006;Karnosky et al, 2003;Liberloo et al, 2009;Norby et al, 2002). Norby et al (2005) analyzed the response of NPP (g C m −2 y −1 ) to elevated [CO 2 ] in four forest FACE experiments and calculated the following regression NPP elev = 1.18×NPP amb + 55.4 (r 2 = 0.97).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated atmospheric CO 2 has been shown to increase rates of photosynthesis and increase productivity (Ceulemans et al, 1999), and in most cases elevated atmospheric CO 2 increases aboveground biomass. However, an increase in belowground biomass greater than the increase in aboveground biomass is often found (Norby et al, 2002;Lukac et al, 2003). To investigate the effects of elevated atmospheric CO 2 on whole ecosystems, Free Air Carbon Dioxide (CO 2 ) Enrichment (FACE) systems have been developed (Hendrey et al, 1999;Miglietta et al, 2001).…”
Section: Introductionmentioning
confidence: 99%